2001
DOI: 10.1051/0004-6361:20010539
|View full text |Cite
|
Sign up to set email alerts
|

The shape of η Carinae and LBV nebulae

Abstract: Abstract. Stellar winds emitted by rotating massive stars may show two main components: firstly bipolar lobes with low density and fast wind, produced by the higher T eff and gravity at the poles ("g eff -effect"); secondly, an equatorial disc with a slow dense wind, produced by the stronger opacities at the equator ("κ-effect"). To see the possible role of this anisotropic wind on the shape of LBV nebulae, we calculate the distribution of the ejected matter in 2 simplified cases: 1) A brief shell ejection. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 20 publications
1
62
0
Order By: Relevance
“…Van Boekel's and our continuum elongation measurements favor the physical model according to which η Car exhibits an enhanced mass loss in polar direction as proposed, for instance, by Owocki et al (1996Owocki et al ( , 1998 or Maeder & Desjacques (2001) for stars rotating close to their critical rotation speed. Axis ratios of the order of 1.2 appear reasonable in the context of such polar-wind models.…”
Section: Elongated Shape Of the Continuum Intensity Distributionsupporting
confidence: 88%
“…Van Boekel's and our continuum elongation measurements favor the physical model according to which η Car exhibits an enhanced mass loss in polar direction as proposed, for instance, by Owocki et al (1996Owocki et al ( , 1998 or Maeder & Desjacques (2001) for stars rotating close to their critical rotation speed. Axis ratios of the order of 1.2 appear reasonable in the context of such polar-wind models.…”
Section: Elongated Shape Of the Continuum Intensity Distributionsupporting
confidence: 88%
“…Kep is the Keplerian velocity on the equator (i.e., the breakup angular velocity). Dwarkadas & Owocki (2002) and Smith et al (2003a), for example, take ¼ 0:9, while Maeder & Desjacques (2001) take ¼ 0:8 0:9. The model presented by Langer et al (1999) is different in that they consider the ratio of luminosity to the Eddington limit.…”
Section: Angg Ular Velocity Evv Olution Duringgthe Great Eruptionmentioning
confidence: 99%
“…Interestingly enough, the group of the B[e] stars shows a two-component stellar wind with a hot, highly ionized, fast wind at the poles and a slow, dense, disk-like wind at the equator (Zickgraf 1989). Maeder & Desjacques (2001) have noticed that the polar lobes and skirt in η Carinae and other LBV stars may naturally result from the g eff and κ-effects. Langer et al (1999) have shown that giant LBV outbursts depend on the initial rotation rate.…”
Section: Results Of Numerical Calculationmentioning
confidence: 99%